Importation of SARS-CoV-2 infection leads to major COVID-19 epidemic in Taiwan (2020)
Objective: COVID-19 has recently become a pandemic affecting many countries worldwide. This study aims to evaluate the current status of COVID-19 in Taiwan and analyze the source of infection. Methods: National data regarding SARS-CoV-2 infection were obtained from Taiwan. CDC at the end of April 2020. These data were subjected to analysis of the current status and correlation between indigenous and imported COVID-19 cases. A phylogenetic tree was created to analyze the phylogeny of Taiwanese SARS-CoV-2 isolates. Results: The first case of SARS-CoV-2 infection in Taiwan was detected on January 21, 2020. Epidemiological data indicate that by April 30, there were a total of 429 COVID-19 confirmed cases with the death rate of 1.3%. Most cases were identified as imported (79.9%; 343/429), with the majority originating from the United States of America (22.1%) and the United Kingdom (17.6%). Results from phylogenetic tree analyses indicate that the Taiwanese SARS-CoV-2 isolates were clustered with the SARS-CoV-2 isolates from other countries (bootstrap value 98%) and sub-clustered with bat SARS-like coronaviruses (bootstrap value 99%). Conclusion: This study suggests that the importation of SARS-CoV-2 infection was the primary risk-factor resulting in the COVID-19 epidemic in Taiwan.